(untitled) (Journal of the Digital Humanities Association of Southern Africa, 2024)
The strategic role of integrating Information and Communication Technologies (ICT) when teaching indigenous languages continues to become increasingly apparent within language planning and policy discourse. The integration of ICT in teaching African languages is a complex and diverse research area, making it challenging to identify common factors that define fundamental methods. The argument put forth is that higher education institutions should invest in implementing continuous and intensive awareness-raising seminars about the value of linguistics, language technology, and practice. This paper aims to investigate a comprehensive plan for emerging digital practices and learning design expertise to enable digital democracy in South African higher education by exploring the various opportunities for integrating technology and African languages. Descriptive themes are developed after an intensive existing literature review and analysis. The Language Management Theory (LMT) guides the paper. The author highlight suggestions to ensure that South Africa meets the 2030 United Nations Sustainable Development Goal number 4, which aims to provide inclusive and quality education for all and promote lifelong learning, primarily using ICTs. By presenting various ICT-based models for education as a transformational approach towards integrating ICTs in teaching African languages, the higher education sector will be revolutionized in the African continent and all developing countries that lack understanding of the power of incorporating technology in teaching and developing native languages. Practice recommendations are also made to ensure successful adaptation to the 4th Industrial Revolution.